Medical Students’ Perspectives on Careers in Hospital Medicine: A National Study - Anne Catherine Miller Cramer; Sandra A. Ham; Yassen Alkaddoumi; Kamel Ibrahim; Shalini T. Reddy; John D. Yoon (MedEdPublish, 2017)
Purpose: Concerns over burnout and other factors may influence whether students pursue hospital medicine as a career. We investigate whether there are certain predictive factors that ultimately play a role in medical students' career interest in hospital medicine.